Granule Nanoparticle Citrus sinensis (L.) Osbeck Peel Lowers Blood Glucose Levels and HbA1C in Alloxan-induced Diabetes Rats - Maya Sari Mutia; Yelvreza Rastiani Sipayung; Dwi Elmiam; Widya Yanti Sihotang; Juliana Lina (The Indonesian Biomedical Journal, 2025)
BACKGROUND: The peel of Citrus sinensis (L.) Osbeck (sunkist orange) peels, which are often seen as waste, actually contains valuable properties such as antioxidants, hypoglycemic, nephroprotective, and anti-inflammatories. The potential effects of C. sinensis peel on diabetes have been discussed but not clear yet. Therefore, this study was performed to evaluate the effects of Granule Nanoparticle Sunkist Peel (GNSP) extracts as an antidiabetic agent in alloxan-induced diabetic rats.METHODS: The nanoparticle suspension was prepared by mixing a formulation of 0.2% chitosan and 0.1% sodium tripolyphosphate. The characteristics of nanoparticles were measured by flow time, tap index and angle of repose. Rats were induced with alloxan injection to create diabetes rat models. Rats were divided into five groups; normal control group, diabetic controls, and diabetic rats receiving either 50, 100, or 200 mg/kg/day GNSP. After 28 days of diabetes induction, rats were euthanized, and blood as well as tissue samples were collected. Blood glucose levels, HbA1c, and histopathology of the liver, kidneys, and pancreas were then assessed.RESULTS: The particle size of the synthesized material was 92.3 nm, which confirmed the nature of nanoparticle. The characteristics of the granule nanoparticle were also in accordance with the standards for drugs suitable for consumption. The administration of GNSP in dose dependent manner significantly decrease blood glucose levels and HbA1C to normal levels compared to control group (p<0.05). Histopathological analysis indicated recovery in pancreas, liver, and kidney tissues following GNSP administration.CONCLUSION: GNSP administration lowers blood glucose levels and HbA1C, as well as improved histopathological condition of pancreas, liver, and kidney in diabetic rats. These findings suggest the potential of utilizing GNSP as a potent antidiabetic agent.KEYWORDS: Citrus Sinensis (L.) Osbeck, histopathology, hyperglycemia, nano medicine, and type 2 diabetes mellitus